Socioeconomics Implications and the Resettlement Action Plan of Alaoji-Onitsha Transmission Line Project on Project Affected Persons - B. U. Uzodinma; I. O. Agbagwa (Archives of Current Research International, 2023)
Resettlement Action Plan (RAP) plays a vital role in managing resettlement-related activities, preventing dispute, agitation and provide necessary component for successful restoration of livelihood of impacted people. Consequently, the study examined the implications of the Resettlement Action Plan (RAP) of Alaoji-Onitsha Transmission Line (TL) project on the socio-economic of the Project Affected Persons (PAPs) in the project corridor using household based questionnaire. The finding on the severity and extent of the project impact on individuals and related socio-economic indicators revealed that 372 households were slated for resettlement, 202 residential buildings, 267 commercial buildings, 11 public buildings, 511.26 hectares of farmland and 42,682 economic trees are impacted by the proposed TL project. The project will have medium residual impacts on land use. The study therefore recommends that the proposed project must ensure resettlement and restoration are carried out in a way that will ensure continuous survival of PAPs with better socio-economic status than the pre-project status.